ANALISIS PELAKSANAAN KINERJA GURU SD NEGERI 94/II MUARA BUNGO - rafai rafai (Jurnal Tunas Pendidikan, 2021)
This study aims to determine teacher performance in the aspects of lesson planning, learning implementation and learning evaluation. This type of research is qualitative research with a descriptive approach. The subjects of this study were teachers of SD Negeri 94 / II Muara Bungo. Research data were obtained through closed questionnaires with a Likert scale. The questionnaire consists of 39 statements. The results showed that the teacher's performance in preparing lesson plans was in the very good category. teacher performance in implementing learning has reached the very good category. Furthermore, for teacher performance in carrying out learning evaluations the majority are still in the good category, there are only two class teachers who have carried out learning evaluations by achieving the very good category. So the performance of teachers at SD Negeri 94 / II Muara Bungo from the aspects of planning, implementing and evaluating learning should always be improved so that the quality of learning is maintained.